Creative literacy in action birth through age nine - Towell, Janet L.; Powell, Katherine C.; Brown, Susannah L. (Australia Cengage Learning, 2018)
"This new early literacy textbook (birth through age nine) focuses on creative literacy instruction through active participation of teachers, parents, and children, providing preservice teachers with practical strategies and activities that can be adapted to meet the needs of diverse learners. It offers a comprehensive view of literacy development and instruction, including assessment, phonemic awareness, and emergent literacy, as well as phonics, vocabulary, reading, writing, and arts integration in diverse classrooms. The authors' holistic approach explains why and how reading and language arts should be taught from the perspective of the whole child, with an emphasis on creativity in a nurturing learning environment. Their unique perspective integrates the arts, educational psychology, and literacy instruction, represented throughout the text by the incorporation of the cognitive, socio-emotional, and physical parts of the self into a visual Holistic Model of Literacy."--Provided by publisher.
1. Theoretical Foundations in Literacy, Psychology, and the Arts -- 2. Emergent and Early Literacy -- 3. Literacy Assessment -- 4. Phonics and Word Identification -- 5. Vocabulary Development and Instruction -- 6. Reading Comprehension -- 7. Writing and Spelling Development -- 8. Family Literacy and Classroom Connections -- 9. Diverse Learners and Literacy -- 10. Teaching Literacy Through the Arts -- Appendix: Integrated Lesson Plans.
Includes bibliographical references (pages 264-272) and index.
Keywords: Language arts; Literacy -- Study and teaching; Reading comprehension